Comparison of Slovak and English Word Stress - Mocova, Lenka (Communications - Scientific letters of the University of Zilina, 2012)
The paper defines and describes the basic stress characteristics in general and shows its functioning in Slovak and English language. It also implies that its wrong perception contributes to Slovak-English language interference.